Is midwifery knowledge a relevant construct in contemporary practice? A report on an international Delphi survey. - MacVane, Fiona (Essentially MIDIRS, 2013)
The author considers the whether there is such a thing as a specific 'midwifery knowledge' and describes how she constructed a Delphi study to explore other people's views on the subject. Includes an explanation of the Delphi method and some of its advantages. Discusses findings of the study.